Enhanced fingerprint classification through modified PCA with SVD and invariant moments - Balti, Ala; Hamdi, Abdelaziz; Abid, Sabeur; Ben Khelifa, Mohamed Moncef; Sayadi, Mounir (Frontiers in Artificial Intelligence, 2024)
This research introduces a novel MOMENTS-SVD vector for fingerprint identification, combining invariant moments and SVD (Singular Value Decomposition), enhanced by a modified PCA (Principal Component Analysis). Our method extracts unique fingerprint features using SVD and invariant moments, followed by classification with Euclidean distance and neural networks. The MOMENTS-SVD vector reduces computational complexity by outperforming current models. Using the Equal Error Rate (EER) and ROC curve, a comparative study across databases (CASIA V5, FVC 2002, 2004, 2006) assesses our method against ResNet, VGG19, Neuro Fuzzy, DCT Features, and Invariant Moments, proving enhanced accuracy and robustness.